Sozialistische Stadt“ versus „europäische Stadt“ –: Urbanisierung und Ruralisierung im östlichen Europa - Bohn, Thomas M. (Comparativ, 2008)
The „Socialist city“ versus the „European city“ – urbanization and ruralization in Eastern Europe In most parts of Eastern Europe the transition from agrarian to industrial societies took place only after World War II. The process of urbanization was influenced by the socialist planning economy. Under this condition, the concept of the “socialist city” found its realization in the modern reconstruction of old historical towns and the foundation of new industrial towns. Today the image of Eastern European capitals consists of monumental centers and monotonous neighborhoods. The development, however, leading to this dichotomy was the result of a lot of contradictions. On the one side, there was a lack of civil society already before the communist seize of power. On the other side, the exodus from the countryside during the period of socialist industrialization lead to a ruralization of already existing cities. At the end the “socialist city” was able to supply its inhabitants with a minimum of dwelling. But it still required the renunciation of urbanity and autonomy.